2013
DOI: 10.1111/ecc.12046
|View full text |Cite
|
Sign up to set email alerts
|

Description and predictors of hospital costs of oesophageal cancer during the first year following diagnosis in Northern Ireland

Abstract: The cost-effectiveness of novel interventions in the treatment of cancer is well researched; however, relatively little attention is paid to the cost of many aspects of routine care. Oesophageal cancer is the ninth most common cancer in the UK and sixth most common cause of cancer death. It usually presents late and has a poor prognosis. The hospital costs incurred by oesophageal cancer patients diagnosed in Northern Ireland in 2005 (n = 198) were determined by review of medical records. The average cost of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…We found that more than 90% of the expenses occurred within 12 months, which was higher than China’s GDP per capita (36,018 CNY in 2011) [ 10 ]. As a comparison, the newly diagnosed medical expenditure was less than 40% of the GDP per capita (2005) in the United Kingdom [ 11 ], less than 60% (2008–2010) in the United States [ 12 ], and less than 65% (1997–2007) in Canada [ 13 ]. According to data from China on the average family population (2.9) and the per capita disposable income (21,810 CNY) of urban households in 2011 [ 10 ], we found that the average medical expenditure per patient for esophageal cancer was 72.9% of the average family annual income for urban households, indicating that the economic burden imposed by esophageal cancer was relatively high for individual patients’ families in China, especially for low-income families.…”
Section: Discussionmentioning
confidence: 99%
“…We found that more than 90% of the expenses occurred within 12 months, which was higher than China’s GDP per capita (36,018 CNY in 2011) [ 10 ]. As a comparison, the newly diagnosed medical expenditure was less than 40% of the GDP per capita (2005) in the United Kingdom [ 11 ], less than 60% (2008–2010) in the United States [ 12 ], and less than 65% (1997–2007) in Canada [ 13 ]. According to data from China on the average family population (2.9) and the per capita disposable income (21,810 CNY) of urban households in 2011 [ 10 ], we found that the average medical expenditure per patient for esophageal cancer was 72.9% of the average family annual income for urban households, indicating that the economic burden imposed by esophageal cancer was relatively high for individual patients’ families in China, especially for low-income families.…”
Section: Discussionmentioning
confidence: 99%
“…The average cost of treating oesophageal cancer is increasing annually (Ho et al 2013). Although we believed early stage of cancer is a significant indicator of better outcome, higher hospital costs were associated with earlier stage of oesophageal cancer in Northern Ireland (Agus et al 2013). To clarify the influence of radiotherapy, we excluded the surgery code in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al ( 4 ) reported that for esophageal cancer, stage II patients had the highest medical expenditure during 2009−2011 in urban China. In terms of hospitalization cost per patient that covered the first year after diagnosis, stage II was the most expensive for esophageal cancer patients in Northern Ireland as well ( 7 ) whereas in Korea, advanced stages at diagnosis were associated with 1.8−2.5 folds higher costs ( 10 ). Compared with patients in US, Chinese stomach cancer patients had larger tumors and later stages ( 32 ), which were generally associated with shorter survival ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these studies were carried out in either one area (county, province) ( 5 , 6 ) or only urban areas ( 4 ). To date, in-depth studies on the cost of illness of stomach or esophageal cancer at patient level have been conducted mainly in developed countries ( 7 - 12 ). In the patients who survived beyond 1 year in Ontario, esophageal cancer was the costliest cancer while stomach cancer was the fifth costliest ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation